2022
DOI: 10.1007/s43440-022-00395-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in regulators of lipid metabolism in the brain: a study of animal models of depression and hypothyroidism

Abstract: Metabolic disturbances in the brain are assumed to be early changes involved in the pathogenesis of depression, and these alterations may be intensified by a deficiency of thyroid hormones. In contrast to glucose metabolism, the link between altered brain lipids and the pathogenesis of depression is poorly understood, therefore in the present study, we determine transcription factors and enzymes regulating cholesterol and fatty acid biosynthesis in the brain structures in an animal model of depression, hypothy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…As expected, inhibition of HMG-CoA reductase by simvastatin also reduced the total cholesterol found in C6 cells, indicating the reliability of the experimental setup. Interestingly, Glombik et al 47 found a reduction in sterol regulatory element-binding protein (SREBP-2), a regulator of cholesterol biosynthesis, but no change in SCD in the hippocampi of WKY rats, an animal model for depression, fitting perfectly to the results in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As expected, inhibition of HMG-CoA reductase by simvastatin also reduced the total cholesterol found in C6 cells, indicating the reliability of the experimental setup. Interestingly, Glombik et al 47 found a reduction in sterol regulatory element-binding protein (SREBP-2), a regulator of cholesterol biosynthesis, but no change in SCD in the hippocampi of WKY rats, an animal model for depression, fitting perfectly to the results in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The 5-HT 1A receptor is a GPCR for which involvement in depression pathology has been shown in multiple studies 51 . In addition, its functionality was demonstrated to be dependent on the cellular cholesterol content 47 , 52 . We therefore investigated whether Ze 117, simvastatin, or dexamethasone not only change the total cellular cholesterol content but also affect the signaling ability of this receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In the central nervous system (CNS), lipid populations play an increasingly recognized role in the maintenance and modulation of energy metabolism, synaptic plasticity, neurotransmission, and regulation of multiple signaling pathways (Hussain et al, 2019 ; Glombik et al, 2022 ). These cascades of biological processes influenced by lipids are associated with a range of emotional behaviors and cognitive functions (Hashimoto et al, 2015 ; Egawa et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the myelin contents of the lateral prefrontal cortex, insula, and whole brain reflect the severity of depression [79]. SREBP-2 was decreased in the hippocampus of an animal model of depression, thereby reducing of cholesterol synthesis [80]. Hypercholesterolaemic mice with knockout of the LDLR show depression-like behaviour and altered monoaminergic metabolism [17].…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%